Role of PFC during retrieval of recognition memory in rodents - Bekinschtein, Pedro Alejandro (2014)
One of the challenges for memory researches is the study of the neurobiology of episodic memory which is defined by the integration of all the different components of experiences that support the conscious recollection of events. The features of episodic memory includes a particular object or person (“what”), the context in which the experience took place (“where”) and the particular time at which the event occurred (“when”). Although episodic memory has been mainly studied in humans, there are many studies that demonstrate these features in non-human animals. Here, we summarize a set of studies that employ different versions of recognition memory tasks in animals to study the role of the medial prefrontal cortex in episodic memory.